Employee Performance Analysis at the Environmental Agency: The Role of Occupational Health and Safety (OHS), Work Environment, and Workload - Andi Pawata (Intensi: Jurnal Riset Manajemen, 2026)
Employee performance in agencies with high field risks is highly dependent on adequate operational protection. This study aims to investigate the impact of Occupational Health and Safety (OHS), work environment, and workload on employee performance at the Environmental Agency of Dompu Regency. The primary issue is the persistent occurrence of workplace accidents and fatigue despite the provision of basic protective facilities. Research question: How do OHS, work environment, and workload empirically affect employee performance at the Environmental Agency of Dompu Regency? The novelty of this study lies in the simultaneous integration of these three determinant factors within the operational context of field workers facing extreme risks in the local government sector. This quantitative research employed a saturated sampling technique, utilizing the entire population of 109 employees as the sample. Primary data were collected using a Likert-scale questionnaire and analyzed using Multiple Linear Regression with the assistance of SPSS software. The empirical findings demonstrate that OHS, work environment, and workload exert a positive and significant impact on employee performance, both partially and simultaneously. In conclusion, ensuring safety guarantees, cultivating a conducive work environment, and allocating a fair proportion of tasks serve as crucial pillars for preventing fatigue and enhancing performance. The implication is that the agency must continuously evaluate and strengthen safety regulations as well as the distribution of daily operational tasks.